2020
DOI: 10.26525/jtfs32.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Payment for Environmental Services: Alleviating the Conflict of Parks Versus People

Abstract: The "parks versus people" conflict is a result of the establishment of protected areas (PAs) that often restrict access to biological resources by the human population, mainly in developing countries. Payment for environmental services (PES) is one of the several strategies that have been developed and implemented in order to mitigate this conflict. This study aimed to evaluate whether PES could smooth the "parks and people" conflict through the analysis of five case studies from different regions and social-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Apoiando-se na segunda compreensão, na perspectiva de Young et al (2010) e Young et al, 2016), os conflitos suscitados na pesquisa se apresentam como oportunidade para o aprimoramento da conservação das UC em questão, por meio da aproximação e estabelecimento da confiança entre raizeiros e órgão ambiental. Para Silveira- Junior et al (2020), ao ser evidenciado, o conflito possibilita o estabelecimento de acordos e arranjos legais entre o poder público e os raizeiros, que vai beneficiar principalmente os objetivos das UC. Também numa perspectiva positiva, os conflitos podem colaborar construindo um caminho único, conforme considerações de Simmel (1986), favorecendo a criação de políticas ambientais que corroborem com as diretrizes da Convenção da Diversidade Biológica, realizada na 2ª Conferência das Nações Unidas para o Meio Ambiente e Desenvolvimento em 1992, na qual ficou estabelecido que os conhecimentos tradicionais deveriam ser protegidos e o uso dos recursos biológicos deveriam ser encorajados, desde que compatíveis com conservação ou utilização sustentável (MMA, 2000).…”
Section: Silveira Junior Et Alunclassified
See 1 more Smart Citation
“…Apoiando-se na segunda compreensão, na perspectiva de Young et al (2010) e Young et al, 2016), os conflitos suscitados na pesquisa se apresentam como oportunidade para o aprimoramento da conservação das UC em questão, por meio da aproximação e estabelecimento da confiança entre raizeiros e órgão ambiental. Para Silveira- Junior et al (2020), ao ser evidenciado, o conflito possibilita o estabelecimento de acordos e arranjos legais entre o poder público e os raizeiros, que vai beneficiar principalmente os objetivos das UC. Também numa perspectiva positiva, os conflitos podem colaborar construindo um caminho único, conforme considerações de Simmel (1986), favorecendo a criação de políticas ambientais que corroborem com as diretrizes da Convenção da Diversidade Biológica, realizada na 2ª Conferência das Nações Unidas para o Meio Ambiente e Desenvolvimento em 1992, na qual ficou estabelecido que os conhecimentos tradicionais deveriam ser protegidos e o uso dos recursos biológicos deveriam ser encorajados, desde que compatíveis com conservação ou utilização sustentável (MMA, 2000).…”
Section: Silveira Junior Et Alunclassified
“…A primeira perspectiva compreende os conflitos como componente integral e positivo da conservação da biodiversidade, como oportunidade de construir confiança entre os envolvidos, ou seja, o reconhecimento da existência dos conflitos e a busca pela sua resolução de forma coletiva pelas partes interessadas (YOUNG et al 2010;YOUNG et al, 2016;SILVEIRA-JUNIOR et al, 2020).…”
Section: Introductionunclassified
“…An alternative to mitigate social confl icts generated by PNA establishment is payment for environmental services (PES). Silveira-Junior et al (2020) found that PES can eff ectively contribute to confl ict resolution. However, PES results diff ered among the study cases due to certain attributes such as local environmental conditions, local economic activities, and stakeholder involvement capacity.…”
Section: Introductionmentioning
confidence: 98%
“…For example, to better understand the ecology of these communities in Brazil Nut groves, it is important to better understand the relationship between the adjacent vegetation and the Brazil Nut trees that are exploited, considering functional attributes and the influence of anthropic collection activities. Because local communities have a strong economic and cultural relationship with Brazil Nut tree exploitation, the sustainable exploitation of this species may be also included in conservation efforts which link environmental regularization and social benefits in Amazonia, such as in Payment for Ecosystems Services (PES) related to carbon stocks (such as in the Voluntary Carbon market), water resources and natural regulatory services (Ribeiro et al, 2018, Silveira-Junior et al, 2020Nonini and Fiala, 2021;Bomfim et al, 2022). Such efforts can enhance ecological restoration success without compromising economic activities and regional cultural practices, consequently contributing to the Amazon rainforest conservation and ecosystem services (Strand et al, 2018, Ribeiro et al, 2018Osaka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%